Classification for Quran authentication using characters and diacritics hashed values - Farida Hazwani Mohd Ridzuan; Madihah Mohd Saudi; Shirzad Z.; Azni A.H. (American Scientific Publishers, 2024)
Indexed by Scopus/ERA